An introduction to Buddhist philosophy - Laumakis, Stephen J. (Cambridge introductions to philosophy, 2024)
"This clearly written text explores the breadth of Buddhist philosophy and its historical unfolding. It considers the basic teachings of the Buddha, and the value of meditation for improving and shaping one's life. This Second Edition includes new chapters on Buddhist ethics and meditative practices for living a flourishing life"--